THE INFLUENCE OF USING E-BOOK EDUCATION ON KNOWLEDGE OF WOMEN UNDER-FREE ABOUT COMPLEMENTARY FOODS AGED 6-12 MONTHS - Nindita Rizkya Wisanto; Gita Kostania, SST., M.Kes; Sri Rahayu, S.Kep. Ns, M.Kes (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2023)
Infants aged 6-24 months are a very vulnerable age because at that age babies experience a period of transition from breast milk to weaning food. If a baby is given complementary food too early or even too late, it will have a negative impact on growth and development, as well as the level of intelligence. Mother's awareness and knowledge about good nutrition for children has an important role in maintaining food quality. For this reason, education about complementary foods is needed which helps mothers access and add information, one of which is by using an e-book about complementary foods for breastfeeding. This study aims to determine the effect of education using e-books on the knowledge of under-aged mothers about complementary foods for breastfeeding aged 6-12 months in the working area of ​​the Ngempit Health Center, Pasuruan Regency. The research design used quantitative research with a pre-experimental method with a one group pretest posttest design. The sample in this study used a purposive sampling technique, in which 56 respondents met the inclusion criteria. Data were obtained using a questionnaire and analyzed using the Wilcoxon signed ranks test. The statistical test results obtained an Asymp.Sig (2-tailed) value of 0.000 <0.05, which means that there is an effect of education using e-books on the knowledge of under-aged mothers about complementary foods for breastfeeding aged 6-12 months in the working area of ​​the Ngempit Health Center, Pasuruan Regency. Based on the results of the research, e-book educational media should be considered as educational media as additional information and changes in behavior in providing complementary feeding.